공급방식에 따른 환경교육 선호에 대한 실증연구 - 강진영; Jinyoung Kang; 홍종호; Hong Jong Ho (환경정책, 2024)
그동안 환경교육은 ‘환경’이라는 공공재를 다룬다는 점에서 국가 차원의 공적 영역이 주로 담당해왔다. 교육서비스는 국가가 주로 공급하기 때문에 공공재로 인식되는 것과 일맥상통한다. 하지만, 환경교육은 준공공재나 가치재, 나아가 사적재로의 특성도 가지고 있다. 이와 같은 환경교육 특성은 환경교육이 우리 사회 안에서 어떻게 공급되는지와 연결되지만, 지금까지 충분히 다루어지지 못하였다. 이 연구는 환경교육의 공급방식을 공적 공급방식과 사적 공급방식으로 구분하고, 공급방식에 따라 독립된 두 집단의 환경교육에 대한 지불의사로 선호를 비교하였다. 두 집단에서 발생할 수 있는 선택표본 편의를 방지하기 위하여 경향점수 매칭 방법을 활용하였으며, 선택편의를 보정한 연구결과 공적 공급방식보다 사적 공급방식에서 약 22.3%가량 지불의사가 높게 나타났다. 이러한 결과는 환경교육이 우리 사회 내에서 충분히 공급되지 않고 있는 현실을 고려할 때 사적 영역을 통한 환경교육의 공급 가능성을 확인한 것으로 볼 수 있다. 이 연구는 공적 공급방식이 아닌 사적 공급방식에 따른 환경교육 가능성을 확인하고, 두 가지 공급방식의 상호협력 가능성을 모색하는 정책 노력 필요성을 시사하고 있다. Environmental education has primarily been the responsibility of the government due to its involvement with the public good―in this case, the environment. Education services, including environmental education, are also predominantly supplied by the government and are perceived as public goods. However, environmental education also has some attributes normally associated with private goods, exhibiting characteristics of quasi-public goods or ‘merit goods’. Although this aspect is related to the supply of environmental education in our society, it has not been adequately addressed. Against this backdrop, this study distinguishes between public and private supply mechanisms of environmental education and compares preferences by analyzing the willingness to pay between two distinct groups based on these supply mechanisms. To mitigate potential selection bias between the two groups, propensity score matching was employed. The research findings, adjusted for selection bias, indicate an approximately 22.3% higher willingness to pay for private supply compared to public supply, with statistical significance observed. These results underscore the potential for private sector involvement in the supply of environmental education. The study emphasizes the need for policy efforts to expand private supply mechanisms beyond public provision and to foster cooperation between the two supply mechanisms.